Platelet‐Derived TGF‐β Induces Tissue Factor Expression via the Smad3 Pathway in Osteosarcoma Cells. (20th July 2018) - Saito, Masanori; Ichikawa, Jiro; Ando, Takashi; Schoenecker, Jonathan G; Ohba, Tetsuro; Koyama, Kensuke; Suzuki‐Inoue, Katsue; Haro, Hirotaka
ABSTRACT: Over the last three decades, the prognosis of osteosarcoma has remained unchanged; the prognosis for patients with lung metastasis is still poor, and the development of new treatments is urgently required. We previously showed that aggressive osteosarcoma cells express more tissue factor (TF) and demonstrate enhanced extrinsic pathway capacity. Furthermore, tumor growth can be suppressed with the anticoagulant low molecular weight heparin. However, the molecular mechanisms underlying TF regulation are still unclear. Here, we report that transforming growth factor‐β (TGF‐β) upregulates TF, which can occur via activated platelets. TF was found to be expressed on osteosarcoma cell surfaces, which mediated the production of Xa and thrombin. TF induction by TGF‐β was observed in several osteosarcoma cells, and especially in MG 63 cells. Both TF expression by TGF‐β and extrinsic pathway activity through TF were rapidly increased. This reaction was inhibited by a TGF‐β type I receptor inhibitor and TGF‐β neutralizing antibody. Although TGF‐β was found to phosphorylate both Smad2 and Smad3, their roles were markedly disparate. Surprisingly, Smad2 knockdown resulted in no inhibitory effect, whereas Smad3 knockdown completely suppressed TGF‐β–induced TF expression. Next, data suggested that platelets were the source of TGF‐β. We confirmed that thrombin‐activated platelets and osteosarcoma cells could release TGF‐β, and that platelet‐derived TGF‐β could induce TF expression. These processes were also inhibited by a TGF‐β type I receptor inhibitor and Smad3 knockdown. Moreover, CD42b, TF, TGF‐β, Smad2/3, and p‐Smad2/3 were also detected in a biopsy sample from an osteosarcoma patient. Collectively, these finding suggested that the interaction between osteosarcoma cells and platelets, via thrombin and TGF‐β, results in a continuous cycle, and that anti‐platelet or anti‐TGF‐β therapy could be a promising tool for disease treatment. © 2018 American Society for Bone and Mineral Research.